Picky Eating Behaviour, Feeding Practices, Dietary Habits, Weight Status and Cognitive Function Among School Children in Kuala Lumpur, Malaysia - Mok, Kai Ting; Tung, Serene En Hui; Satvinder Kaur (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2022)
Introduction: Picky eating behaviour was linked to nutritional problems due to limited dietary variety. This study aimed to determine the causes and consequences associated with picky eating behaviour among school-aged children in Kuala Lumpur, Malaysia. Methods: A total of 339 children aged seven to nine years participated in this cross-sectional study. Socio-demographic factors, eating behaviours and child/ parental feeding style were assessed through parent’s questionnaires, while eating habits of children were accessed through child’s questionnaire. Body height and weight were measured; body mass index (BMI) was calculated. Cognitive function level was determined using the Raven’s Coloured Progressive Matrices test. Results: One third (38%) of the children were picky eaters and consumed lesser vegetables (χ2 =4.49,p=0.034) and fish (χ2 =5.55,p=0.019), but more milk and dairy products (χ2 =3.91,p=0.048), snacks (χ2 =6.25,p=0.012) and fast food (χ2 =7.35,p=0.007) compared to non-picky eaters. Picky eaters were more likely to have normal weight status based on weight-for-age, height-for-age and BMI-for-age compared to non-picky eaters (p<0.05). Picky eaters came from a household with other picky eaters in the family and their parents tend to use an instrumental feeding style. Picky eaters had a poorer cognitive function compared to non-picky eaters (p=0.03). Conclusion: We did not find significant differences in growth parameters between picky and non-picky eaters but picky eaters were more likely to have a poorer cognitive function. As parental feeding styles significantly influenced children’s eating behaviour, interventions should target parents to improve their children’s dietary variety.